2017
DOI: 10.18632/oncotarget.15636
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol suppresses solar ultraviolet-induced skin inflammation by targeting T-LAK cell-originated protein kinase

Abstract: Excessive exposure to solar UV (SUV) is related with numerous human skin disorders, such as skin inflammation, photoaging and carcinogenesis. T-LAK cell- originated protein kinase (TOPK), an upstream of p38 mitogen-activated protein kinase (p38) and c-Jun N-terminal kinases (JNKs), plays an important role in SUV -induced skin inflammation, and targeting TOPK has already been a strategy to prevent skin inflammation. In this study, we found that the expression of TOPK, phosphorylation of p38 or JNKs was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…Furthermore, targeting TOPK has been a strategy to prevent solar-related inflammation ( Xue et al, 2017 ), and 3-DSC showed anti-inflammatory effects in previous research ( Kim et al, 2014 ). In our study, we also found that 3-DSC prevented skin thickening, which was induced by acute SSL ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, targeting TOPK has been a strategy to prevent solar-related inflammation ( Xue et al, 2017 ), and 3-DSC showed anti-inflammatory effects in previous research ( Kim et al, 2014 ). In our study, we also found that 3-DSC prevented skin thickening, which was induced by acute SSL ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Excess solar ultraviolet (SUV) radiation is the dominant risk factor for skin cancer ( Ratushny et al, 2012 ; Gao et al, 2017 ). It has been suggested that acute solar-simulated light (SSL) irradiation enhances T-lymphokine-activated killer cell-originated protein kinase (TOPK) expression and induces inflammation in SKH1 mice dorsal skin ( Xue et al, 2017 ; Roh et al, 2018 ). Therefore, targeting TOPK may be a promising strategy for skin cancer prevention and treatment ( Gao et al, 2017 ; Roh et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various clinical observations have reported the treatment effect of Cynanchum paniculatum in dermatological diseases. In vivo and in vitro studies suggested a protective role of paeonol against solar ultraviolet- (SUV-) induced skin inflammation via targeting T-LAK cell-originated protein kinase (TOPK), an upstream of p38 kinases and JNKs [ 92 ]. Furthermore, paeonol inhibits IL-6 and TNF- α secretion in a skin inflammation mouse model [ 93 ].…”
Section: Modulation Of Inflammation By Cynanchum Paniculmentioning
confidence: 99%
“…[ 17 ] Recent works have shown that paeonol can regulate inflammatory factors (interleukin [IL]-6, TNF-α) and inhibit inflammatory reaction; improve the protein content of JNKs, H2AX, TOPK, and p38 through p38MAPK and JNKs signaling pathway. [ 18 ] Gypenosides can inhibit the secretion of inflammatory factors (IL-6, TNF-α, IL-1β) from HaCaT cells damaged by light. Salvianolic acid B can reduce hydroxyproline content, superoxide dismutase activity, and the formation of free radical metabolites.…”
Section: Introductionmentioning
confidence: 99%